2021
DOI: 10.1016/j.jseint.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative navigation and preoperative templating software are associated with increased glenoid baseplate screw length and use of augmented baseplates in reverse total shoulder arthroplasty

Abstract: Background Preoperative templating software and intraoperative navigation have the potential to impact baseplate augmentation utilization and increase screw length for baseplate fixation in reverse total shoulder arthroplasty (rTSA). We aimed to assess their impact on the (1) baseplate screw length, (2) number of screws used, and (3) frequency of augmented baseplate use in navigated rTSA. Methods We compared 51 patients who underwent navigated rTSA with 63 controls who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
(4 reference statements)
1
30
0
Order By: Relevance
“…Other findings include an increased number of augmented glenoid implants in both ATSA and RTSA navigated cohorts and a decreased number of baseplate screws in the RTSA navigated cohort when intraoperative navigation was used, which has also been observed in other studies 4,5 .…”
Section: Discussionsupporting
confidence: 73%
“…Other findings include an increased number of augmented glenoid implants in both ATSA and RTSA navigated cohorts and a decreased number of baseplate screws in the RTSA navigated cohort when intraoperative navigation was used, which has also been observed in other studies 4,5 .…”
Section: Discussionsupporting
confidence: 73%
“… 11 Sprowls et al. 19 evaluated a computational navigation system combined with patients’ preoperatory images in real time. The authors confirmed that a better placement of baseplate screws was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…However, this requires learning time. 24 The major limitation of our study was limited number of enrolled patients. A larger sample size would have been able to test for more precise interactions between independent variables.…”
Section: Case Seriesmentioning
confidence: 94%